Tergeraklah Hatinya oleh Belas Kasihan Belajar dari Perumpamaan Orang Samaria yang Murah Hati (Luk 10:25-37) dalam Mengasihi Embrio Manusia sebagai Sesama - Benny Phang (Studia Philosophica et Theologica, 2019)
Jesus’ teaching on the love of neighbor is excellently presented in the parable of the Good Samaritan. This parable elaborates narratively Jesus’ understanding of the love of neighbor. Learning from Jesus’ teaching from this parable, we can learn how to put in practice the love of neighbor which is surpassing all categories. This discussion and elaboration on the love of neighbor provides a biblical-theological insight into the personhood of the early human embryo. It also helps us to understand how to exercise our personal engagement to the early human embryo as an expression of the love of neighbor.